SMEs: Diversifying the Economy Beyond Hydrocarbons through International Marketing - Abdelhafid HARHOUZ; Ahmed KOUIDRI; Badreddine LAIFAOUI (Pensées Genre, Penser Autrement)
The world has witnessed various changes that have prompted small and medium-sized enterprises (SMEs) to reassess their strategies, shifting their focus from merely achieving profits to adapting to an increasingly competitive environment. This study aims to explore the importance of international marketing for these enterprises, particularly in rentier states like Algeria, which is striving to diversify its non-oil exports. The results showed that success in global markets requires understanding consumer needs and meeting those needs through effective marketing strategies. Therefore, Algeria needs a new vision that aligns with the global economic system to enhance its competitiveness and achieve its developmental goals.